Safety of the functional food product - canned "dessert from topinambur" in the process of its manufacture - L. K. Patsyuk; T. V. Fedosenko; D. V. Zhuravskaya-Skalova (Аграрная наука Евро-Северо-Востока)
In this article potentially dangerous factors that may arise during making canned products are determined on basis of the analysis of the technological process in the production of a new type of functional product “Dessert from topinambur” and the probability and reasons for the occurrence of these factors are proved. Based on the dangerous factors determined, a block diagram of these cans’ technological process control was worked out. In this block diagram, the main critical and control-critical points are set up at the corresponding manufacturing stages throughout the entire technological process of product development. In addition, the severity of the consequences from the appearance of these dangerous factors and the ways of their elimination are estimated. The severity of the consequences for different factors is different. It can be insignificant, because the dangerous factors that cause it can be corrected after identifying and eliminating their reason. They can be attributed to “not very significant.” Therefore, a checkpoint is set in this operation. The severity of the consequences from other dangerous factors can be very significant and lead to diseases and even poisonings, so a critical control point is set here. The developed block diagram of the monitoring the technological process of the production of a new type of functional product “Dessert from topinambur” and “The map of critical control points to be monitored” established by the diagram allow to carry out the monitoring of the total production process of manufacturing safe food product according to the principles of HACCP.